Catalytic effect of nickel phthalocyanine on hydrogen storage properties of magnesium hydride: Experimental and first-principles studies. (23rd November 2017) - Zhang, J.; Qu, H.; Yan, S.; Wu, G.; Yu, X.F.; Zhou, D.W.
Abstract: The high dehydrogenation temperature of magnesium hydride MgH2 is still the main obstacle to its practical application as a solid-state hydrogen storage medium. Using experimental and first-principles calculations approaches, we, for the first time, investigate the catalytic effect and mechanism of nickel phthalocyanine on the dehydrogenation properties of MgH2 . The results display that a small amount of nickel phthalocyanine can promote MgH2 dehydrogenation at significantly decreased temperatures by more than 90 °C relative to milled pristine or graphene-added MgH2 system. However, the agglomeration of MgH2 particles is not evidently alleviated through nickel phthalocyanine addition. When MgH2 is milled with graphene firstly and then the obtained mixture is further milled with nickel phthalocyanine, the dehydrogenation properties and agglomeration of MgH2 particles can be synergistically improved to some extent. The first-principles calculations of dehydrogenation enthalpy and binding energy account for the experimental differences in catalysis and aggregation-resistance abilities of nickel phthalocyanine and graphene on MgH2 particles. Notably, the NiN4 -inserted graphene is predicted to be an ideal additive for MgH2, which combines the synergetic catalysis-confinement effect of nickel phthalocyanine and graphene on MgH2 particles. Analysis of electronic structures reveals that the excellent catalytic effect of nickel phthalocyanine on MgH2 can be ascribed to the more electron transfer between nickel phthalocyanine and MgH2, which induces the significantly weakened bond strength of MgH and decreased dehydrogenation enthalpy of MgH2 . Graphical abstract: Highlights: NiPc exhibits superior catalytic effect on MgH2 dehydrogenation. Multi-addition of NiPc and G can improve dehydrogenation and agglomeration of MgH2 . Dehydrogenation enthalpy and binding energy of MgH2 -NiPc system are calculated. Catalytic effect of NiPc on MgH2 is associated with electron transfer between them. NiN4 -inserted G is predicted to be an ideal catalysis-confinement additive for MgH2 .